Characteristics Of Microbubbles Generated From Perforated Plates - Dhyna Analyes Trirahayu; Ridwan P. Putra; Joshua Mulia Nababan; Mubiar Purwasasmita (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2022)
Microbubbles are emerging as versatile tools in numerous scientific and engineering disciplines. However, the applications of microbubbles in agricultural fields require a simple and cost-effective device that can be used to generate microbubbles. In this study, a new approach to producing microbubbles was developed using perforated plates incorporated with glass columns. Two different plates with various numbers of holes were fabricated. Characterization of the microbubbles showed that the diameter of the microbubbles produced was in the range of 10.4 to 21.1 µm. The gas-liquid ratio tended to increase by around 30-40%, with increasing oxygen gas flow rate and gas-jetting time. The enhanced oxygen gas flow rate and gas-jetting time also prolonged the residence time of the microbubbles. In general, this technique is promising that can be implemented in agricultural sectors, especially in hydroponic systems.